The geotectonic environments of Early Precambrian granulites in Brazil - Wernick, Eberhard [UNESP]; De Almeida, Fernando F.M. (Elsevier, 1979)
A review is presented concerning Archaean granulites occurring in some old domains of the South American Platform, which was consolidated at the end of the Brazilian Cycle (900-500 Ma). The rocks occur in different geotectonic environments and show variable ages, structures and lithological associations. The most important complexes are the Atlantic Granulite Belt in the São Francisco Craton and the Goias Granulite Belt in the Central Goias Massif, both several hundred kilometres long. The former is composed of the Caraibas Complex, the Jequié Complex, the Salvador Complex and several minor granulite occurrences along the Brazilian coast in the States of Espírito Santo and Rio de Janeiro. The latter includes the large basic-ultrabasic complexes of Barro Alto, Tocantins and Canabrava. Both belts consist of massive or foliated rocks, banded or homogeneous and varying from acidic to ultrabasic in composition. They are the result of metamorphism affecting diversified supra- and infracrustal material. The Atlantic Granulite Belt lies between greenstone/granite terrains which show ovoid and boomerang-type dome structures. The contacts between both are either tectonic or transitional. Another occurrence of Archaean granulites comprises intercalations of palaeosomes and melanosomes within migmatites and anatectic rocks. These vary in size from small lenses to irregular complexes which may attain sizes of several hundred square kilometres. Apart from migmatites, they are associated with gneisses, schists and granitoid bodies. They are located in regions which underwent remobilization of varying intensity during the Middle and Late Precambrian. The rocks show polymetamorphism, K-feldspar blastesis, tectonic overprinting and isotopic rejuvenation. These granulites are in some cases very similar to those formed during the Middle Precambrian. In some places it is therefore quite difficult to distinguish between Early and Middle Precambrian granulites - the more so, since interpretations of radiometric age values are largely controversial. At present there is no evidence of granulitic rocks related to the Late Precambrian geotectonic cycles of Brazil. © 1979.